Rising powers and the Arab-Israeli conflict since 1947 - Burton, Guy (Lexington Books, 2018)
By studying the actions of the rising powers in relation to the Arab-Israeli conflict since 1947, this book identifies active and passive approaches to conflict management. Through them, this book examines the extent to which these actions help or hinder aspirations to greater global influence.